2018
DOI: 10.1016/j.shaw.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coping and Communication Skills Program on Physician Burnout, Quality of Life, and Emotional Flooding

Abstract: BackgroundPhysician behaviors that undermine a culture of safety have gained increasing attention as health-care organizations strive to create a culture of safety and reduce medical errors. We developed, implemented, and assessed a course to teach physicians skills regarding effective coping and interpersonal communication skills and present our results regarding outcomes.MethodsWe examined a professional development program specifically designed to address unprofessional or distressed behaviors of physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Positive thinking or optimism was found to reduce stress and exhaustion among HCW in Turkey during COVID-19 [ 59 ]. However, similar to a study by Chor et al (2020), some HCW resorted to maladaptive coping; coping skills intervention may play some role in addressing burnout among HCW [ 60 ]. Many HCW described physical impacts, followed by occupational, psychological, and social impacts, and this seems to be consistent with a study in Italy that reported irritability, appetite change, sleep disturbance, muscle tension, and exaggerated reactions as the major perceived impacts among its HCW [ 45 ].…”
Section: Discussionmentioning
confidence: 82%
“…Positive thinking or optimism was found to reduce stress and exhaustion among HCW in Turkey during COVID-19 [ 59 ]. However, similar to a study by Chor et al (2020), some HCW resorted to maladaptive coping; coping skills intervention may play some role in addressing burnout among HCW [ 60 ]. Many HCW described physical impacts, followed by occupational, psychological, and social impacts, and this seems to be consistent with a study in Italy that reported irritability, appetite change, sleep disturbance, muscle tension, and exaggerated reactions as the major perceived impacts among its HCW [ 45 ].…”
Section: Discussionmentioning
confidence: 82%
“…To facilitate coping abilities, interventions to accelerate adaptive coping may be conducted for healthcare providers during times of the COVID-19 crisis. For example, a coping-enhancing program called Effective Coping and Communication Skills for Physicians showed significant efficacy in improving healthcare providers' stress management skills and decreasing the level of emotional exhaustion [ 40 ]. Future intervention may benefit from tailoring and adapting this program for HIV healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…The patient benefits through engagement and trust with the clinician, getting their needs addressed, receiving clear information, and a mutual set of goals and treatment. By learning effective communication skills, the clinician gains satisfaction and meaningfulness 28 in the clinical practice, and with reduced emotional exhaustion, and burnout 29,30 . Finally, regarding the outcome, an effective patient-provider interaction reduces the patient's symptom severity and emotional distress and improves the patient's quality of life and coping and with reduced use of healthcare services 24,31,32 .…”
Section: Benefits the Patient Provider And Clinical Outcomementioning
confidence: 99%